2017
DOI: 10.3390/ijms18020283
|View full text |Cite
|
Sign up to set email alerts
|

Early Healing Events after Periodontal Surgery: Observations on Soft Tissue Healing, Microcirculation, and Wound Fluid Cytokine Levels

Abstract: Early wound healing after periodontal surgery with or without enamel matrix derivative/biphasic calcium phosphate (EMD/BCP) was characterized in terms of soft tissue closure, changes of microcirculation, and expression of pro- and anti-inflammatory cytokines in gingival crevicular fluid/wound fluid (GCF/WF). Periodontal surgery was carried out in 30 patients (18 patients: application of EMD/BCP for regeneration of bony defects; 12 patients: surgical crown lengthening (SCL)). Healthy sites were observed as untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Whether this is an early indication of changes within the GT to an anti‐inflammatory and wound healing cytokine profile is unclear. Anti‐inflammatory cytokine levels fall immediately after and remain depressed for several days following periodontal flap surgery, while levels of IL‐1β and TNF‐α are increased during the initial phases of wound healing . Anti‐inflammatory cytokines have been shown to play a key role in the disease process, and along with the proinflammatory cytokines, they are implicated in the healing process .…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is an early indication of changes within the GT to an anti‐inflammatory and wound healing cytokine profile is unclear. Anti‐inflammatory cytokine levels fall immediately after and remain depressed for several days following periodontal flap surgery, while levels of IL‐1β and TNF‐α are increased during the initial phases of wound healing . Anti‐inflammatory cytokines have been shown to play a key role in the disease process, and along with the proinflammatory cytokines, they are implicated in the healing process .…”
Section: Discussionmentioning
confidence: 99%
“…In the hemostasis phase (i) the volume of the graft occupies the space and thus reduces the volume of the blood clot, and in doing so, the number of viable cells that reside within the site. This phenomenon in the cleaning inflammatory phase leads to a reduction in the products of the macrophages degradation, which are important mediators for the conversion towards the proliferation phase (ii) [28]. In the regeneration phase (iii), angiogenesis, being the essential element in the production of the collagen matrix, may be disturbed by the barrier effect of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is known that the total amount of cytokines varies based on the volume of GCF, the concentration instead of the total amount was considered . For the present study, IL‐1β and IL‐8 were chosen as two pro‐inflammatory cytokines involved in early inflammatory processes related to wound healing . IL‐1β induces periodontal inflammation and controls the extracellular matrix degradation activity of the plasminogen activator system during inflammation and wound healing .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures trigger metabolic and immunologic reactions that lead to a rise in pro‐inflammatory cytokines . It has been demonstrated that evaluation of cytokine levels in wound fluids is a sensitive and specific assessment of inflammation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation